2007
DOI: 10.1007/s11912-007-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from clinical to biologic indicators of prognosis after resection of hepatic colorectal metastases

Abstract: Following resection of hepatic colorectal metastases, there are few criteria for predicting which patients have more aggressive disease and are, therefore, more likely to experience recurrence and reduced survival. Traditionally, primary tumor stage, preoperative carcinoembryonic antigen level, time from primary tumor treatment to diagnosis of hepatic metastases (disease-free interval), hepatic tumor size, number of hepatic metastases, and presence of extrahepatic disease have been reported to be predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…[8][9][10] In fact, high levels of pre-hepatectomy CEA have been associated with long-term post-operative outcomes and have been incorporated into clinical risk scores. 5,6,[11][12][13] Many of these studies have, however, reported different pre-operative CEA cut-off levels (i.e. >5, 10, >30, >60, >100 and >200 ng/mL) as being independently predictive of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In fact, high levels of pre-hepatectomy CEA have been associated with long-term post-operative outcomes and have been incorporated into clinical risk scores. 5,6,[11][12][13] Many of these studies have, however, reported different pre-operative CEA cut-off levels (i.e. >5, 10, >30, >60, >100 and >200 ng/mL) as being independently predictive of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of clinical outcome following liver resection have been thoroughly investigated and include the following: Primary tumour grade; number and size of liver metastases and whether they are synchronous or metachronous; period of disease-free survival; presence of extrahepatic disease; and resection margin (6,7). These parameters have significant limitations and are based on population data rather than being individualized for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the need for a new prognostic model that uses biologic and clinicopathologic factors to guide treatment of the patients with SCLM (11,12).…”
mentioning
confidence: 99%
“…This underscores the need for a new prognostic model that uses biologic and clinicopathologic factors to guide treatment of the patients with SCLM (11,12). 18 F-FDG PET/CT uses the increased rates of glucose metabolism in tumors to characterize the biology of different cancers, with several studies having reported that high rates of 18 F-FDG uptake in tumors are associated with increased aggressiveness and poor survival (13,14).…”
mentioning
confidence: 99%